Properties of Modestobacter deserti sp. nov., a Kind of Novel Phosphate-Solubilizing Actinobacteria Inhabited in the Desert Biological Soil Crusts - Jiang, Zhu-Ming; Zhang, Bing-Huo; Sun, Hong-Min; Zhang, Tao; Yu, Li-Yan; Zhang, Yu-Qin (Frontiers in Microbiology, 2021)
Three Gram-staining-positive, aerobic, motile actinobacterial strains designated as CPCC 205119T, CPCC 205215 and CPCC 205251 were isolated from different biological soil crust samples collected from Tengger Desert, China. The 16S rRNA gene sequence comparison of these three strains showed they had almost identical 16S rRNA genes, which were closely related to members of the family Geodermatophilaceae, with the highest similarities of 96.3-97.3 % to the species of Modestobacter. In the phylogenetic tree based on 16S rRNA gene sequences, these isolates clustered into a subclade next to the branch containing the species of Modestobacter lapidis and Modestobacter multiseptatus, within the lineage of the genus Modestobacter. The comparative genomic characteristics (values of ANI, dDDH, AAI and POCP) and the phenotypic properties (morphological, physiological and chemotaxonomic characteristics) of these isolates, readily supported to affiliate them to the genus Modestobacter as a single separate species. For which we proposed that the isolates CPCC 205119T, CPCC 205215 and CPCC 205251 represent a novel species of the genus Modestobacter as Modestobacter deserti sp. nov.. CPCC 205119T (=I12A-02624 =NBRC 113528T =KCTC 49201T) is the type strain. The genome of strain CPCC 205119T consisted of one chromosome (4,843,235 bp) containing 4,424 coding genes, 48 tRNA genes, 5 rRNA genes, 3 other ncRNA genes and 101 pseudogenes, with G+C content of 74.7 %. The whole-genome sequences analysis indicated that this species contained alkaline phosphatase gene (phoA), phosphate transport-related genes (phoU, phnC, phnD, ppk, pstA, pstB, pstC, pstI), trehalose-phosphate synthase gene (otsA), trehalose 6-phosphate phosphatase gene (otsB) and other encoding genes for the properties that help the microorganisms adapt to harsh environmental conditions prevalent in deserts. Strains of this species could solubilize tricalcium phosphate (Ca3(PO4)2) and phytin, assimilate pyrophosphate, thiophosphate, dithiophosphate, phosphoenol pyruvate, 2-deoxy-D-glucose 6-phosphate and cysteamine-S-phosphate.